'Lysinibacillus saudimassiliensis' sp. nov., a new bacterial species isolated from air samples in the urban environment of Makkah, Saudi Arabia. (March 2017) - Papadioti, A.; Azhar, E.I.; Bibi, F.; Jiman-Fatani, A.; Aboushoushah, S.M.; Yasir, M.; Raoult, D.; Angelakis, E.
Abstract: We report here the main characteristics of ' Lysinibacillus saudimassiliensis ' strain 13S34_air τ (CSUR = P1222), a new species of the Lysinibacillus genus that was isolated from air samples in the city environment of Makkah, Saudi Arabia, during the pilgrim period of Hajj 2012.